Pengembangan Sistem Monitoring dan Kendali Pertumbuhan Tanaman Semangka Dengan TCS230 Berbasis IOT - abdur rohman wakhid (Universitas Muhammadiyah Surabaya, 2022)
Watermelon plants are plants that require full sun exposure and lots of water for the continuity of the photosynthesis process, watermelon plants need water continuously and should not be deficient, lack of water can hinder the watermelon plant development process and as for other factors that can inhibit the watermelon plant growth process. is the presence of leaf disease in watermelon plants, these factors must be considered because later they will affect the yields obtained by watermelon farmers. To help farmers overcome these problems, a tool called Development Monitoring and Control System for Watermelon Plant Growth is based on TCS230. This IoT tool uses Arduino Uno as the main control and this tool consists of several sensors that will detect several parameters to support the achievement of watermelon plant growth requirements, this tool uses a TCS230 color sensor which will It detects disease on watermelon leaves and the results of leaf disease identification will activate the drug pump if diseased leaves are found, this tool also uses a DHT11 sensor to detect the level of soil moisture and the results of the identification of soil moisture will be sent to a water pump and will activate the water pump. if watermelon plants experience drought, this tool is able to identify 2 leaf diseases on watermelon plants, namely anthracnose, and leaf spot, in this prototype there are 3 pumps containing water, drug 1, and drug 2, the results of all identification and monitoring sensors will be displayed on the screen. 2x16 LCD screen and sent to the blynk application in real time on the farmer's smartphone via the IOT network